Estimating missed government tax revenue from foreign tobacco: survey of discarded cigarette packs. Issue 5 (30th July 2009) - Wilson, N; Thomson, G; Edwards, R; Peace, J
Abstract : Aim: To clarify the extent of use of foreign (including duty free, foreign normal retail and smuggled) tobacco, and to estimate missed government tax revenue in a geographically isolated country. Methods: Discarded cigarette packs were collected on the streets of four cities and six New Zealand towns/rural locations between November 2008 and January 2009. Results: Out of a total of 1310 packs collected, 42 foreign packs were identified (3.2%, 95% CI 2.4% to 4.3%). Overall, the distribution of packs by country and company was not suggestive of any clustering that might indicate smuggling. At 3.2% of packs being "foreign", the New Zealand government is losing around $36 million per year in tobacco-related tax relative to if all this tobacco was purchased in New Zealand. For various reasons (including that it was not possible to identify packs bought duty free within New Zealand, and other New Zealand survey data indicating duty free product use at 3.8% of packs), the figure reached is probably an underestimate of the true level. Conclusion: The New Zealand government is missing out on revenue that could be used for improving the funding of tobacco control, and smokers are being exposed to cheaper tobacco thus increasing their risk of continuing to smoke. This government and other governments can and should act at the international and national levels to end the sales of duty free tobacco.